Investasi dalam Perspektif Ekonomi Islam: Pendekatan Teoritis dan Empiris - Pardiansyah, Elif (Economica: Jurnal Ekonomi Islam, 2017)
Investment is a commitment to withhold excess funds in order to gain profit in the future. Nevertheless, there are unscrupulous individuals who utilize investment as a means of collecting funds from the public with products and activities that are not according to sharia. Therefore, explaining the principles of sharia in investing becomes important as a guide for society. Eclpisit and implicit investment activities contained in the number of Qurâanic verses and the sunnah of the Prophet Muhammad, who once ran the business and became a partner of the Mecca investor of his day. The principle of sharia investment is any form of muamalah may be done until there is a prohibited prohibition, the water search for forbidden activities in a business activity, both object (product) and the process of activity that contains elements haram, gharÄr, maysÄ«r, ribÄ, tadlÄ«s, talaqqÄ« al-rukbÄn, ghabn, á¸arar, rishwah, maksiat and áºulm. In investing, there are sharia rules regarding what covenants are allowed, what is prohibited, and risks that arise as an integral part of investment activity.